Anticholinergics and falls in older adults - Xu, Xiang Jiang; Tan, Maw Pin * (Taylor and Francis, 2022)
Introduction: The use of medications with anticholinergic (ACh) properties is associated with numerous adverse effects especially in older adults. Emerging evidence suggests the presence of long-term effects with ACh use.